Managing Scoliosis in a Young Child with Rett Syndrome: A Case Study - Meir Lotan; Joav Merrick; Eli Carmeli (The Scientific World Journal)
Rett syndrome is a genetic disorder primarily affecting females. One of its most disabling features is the severe and rapid progression of scoliosis. So far, only surgical intervention has succeeded in reversing the development of scoliosis in Rett syndrome.The present study describes a new management approach implemented with a girl with Rett syndrome. The core of the management regime was intensive: asymmetrical activation of trunk muscles through equilibrium reactions. The X-rays accompanying the article (evaluated by four experienced orthopedic surgeons blinded to the intervention process) suggested that the intervention was successful in reversing the progress of the scoliosis for the above-mentioned child. Discontinuation of treatment led to severe and rapid deterioration of the spinal curve.Due to the fact that this was a case study, generalization is limited, but we suggest further investigation and studies with this method.